2022
DOI: 10.1021/acs.nanolett.2c03614
|View full text |Cite
|
Sign up to set email alerts
|

Directly Observing the Evolution of Flexoelectricity at the Tip of Nanocracks

Abstract: As an electromechanical coupling between strain gradients and polarization, flexoelectricity is largely enhanced at the nanoscale. However, directly observing the evolution of flexoelectric fields at the nanoscale usually suffers from the difficulty of producing strain gradients and probing electrical responses simultaneously. Here, we introduce nanocracks in SrTiO 3, Ba 0.67 Sr 0.33 TiO 3, and TiO 2 samples and apply continuously varying mechanical loading to them, and as a result, huge strain gradients appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…20,21 In addition to the ease of preparation and physical-chemical stability enabling its use in various occasions, the unique electronic structure and higher intrinsic carrier concentration are significant factors. 22,23 For example, He et al have fabricated TiO 2 @MAPbI 3 nanoarrays with decent photovoltaic response, 24 and Zheng et al have fabricated n-TiO 2 /p-NiO heterojunctions for achieving remarkable self-powered UV photodetectors. 25 Compared with conventional film photovoltaic devices, orderly nanoarrays can further increase the solar efficiency and stability via its microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 In addition to the ease of preparation and physical-chemical stability enabling its use in various occasions, the unique electronic structure and higher intrinsic carrier concentration are significant factors. 22,23 For example, He et al have fabricated TiO 2 @MAPbI 3 nanoarrays with decent photovoltaic response, 24 and Zheng et al have fabricated n-TiO 2 /p-NiO heterojunctions for achieving remarkable self-powered UV photodetectors. 25 Compared with conventional film photovoltaic devices, orderly nanoarrays can further increase the solar efficiency and stability via its microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been several reports on an emergent phenomena from nanocracks in insulating oxide materials. For examples, Abdollahi et al . theoretically predicted the relationship between the direction of the polar axis and crack propagation in the piezoelectric material .…”
mentioning
confidence: 99%
“…showed the evolution of strain relaxation and their flexoelectricity. 15 Yeo et al . reported that the electrical conductivity near the STO crack wall could be enhanced by a factor of 10 4 by the migration of oxygen vacancies.…”
mentioning
confidence: 99%
See 2 more Smart Citations